2013
DOI: 10.6116/kjh.2013.28.6.71
|View full text |Cite
|
Sign up to set email alerts
|

The comparisons of Lycii Radicis Cortex and Corni Fructus water extract effects on streptozotocin-induced diabetes in rats

Abstract: Objectives : This study aimed to compare the anti-diabetic efficacy of Lycii Radicis Cortex (Lycium chinense Mill.) and Corni Fructus (Cornus officinalis) on streptozotocin (STZ)-induced diabetes in rats.Methods : Male Sprague-Dawley rats were divided into four groups; normal, STZ-control, Lycii Radicis Cortex extract-administrated group (LRC) and Corni Fructus extract-administrated group(CF). Diabetes in rats was induced by intraperitonal injection with streptozotocin (STZ) at doses of, 30 ㎎/㎏ (body weight) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…It was observed that blood glucose levels dropped in STZ‐induced diabetic mice fed a 0.4% silkworm group (Kim et al, 2007). In addition, hyperglycaemia was observed to be under control in STZ‐treated rats when injected with silkworm ethanol extract (Han et al, 2002). These results impressively demonstrated the importance of silkworms in regulating hyperglycaemia in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that blood glucose levels dropped in STZ‐induced diabetic mice fed a 0.4% silkworm group (Kim et al, 2007). In addition, hyperglycaemia was observed to be under control in STZ‐treated rats when injected with silkworm ethanol extract (Han et al, 2002). These results impressively demonstrated the importance of silkworms in regulating hyperglycaemia in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…동의보감 신형문 9) 에서 삼정환(Samjung-hwan)은 "오랫 , 항산화 효과 12) , 면역개 14) . 또한 삼정환의 구성 약재인 창출(Atractylodes japonica)의 지질대사 개선 효과 15) , 지골 피(Cortex lycii radicis)의 혈당강하, 혈압강압 효과 16,17) , 상 심자(Morus alba Linne)의 항산화 효과 18,19) (Fig. 1, 2).…”
unclassified
“…또한 삼정환의 구성 약재인 창출(Atractylodes japonica) 8,9) , 지골피(Cortex lycii radicis) [10][11][12][13] , 상심자(Morus alba Linne) …”
unclassified